Sponsorshaping: How a Teacher Used Sponsors of Literacy for Pedagogical Purposes - Ryan Dippre (Networks: An Online Journal for Teacher Research, 2016)
Historically, the actions of classroom teachers have had a massive impact on the implementation of top-down reform efforts. However, a pedagogically-friendly construct for considering this impact has been lacking in studies of teacher practice. In this article, I draw on Deborah Brandt’s concept of sponsors of literacy to build a construct for thinking about teacher actions with, against, and through the social and historical forces that work their way into the classroom: sponsorshaping. Through a grounded theory analysis of six different types of documents used in an Advanced English 11 writing classroom, I show how sponsors of literacy were “shaped” with and against each other through the authorial decisions of the teacher. Drawing on these results, I suggest ways in which sponsorshaping can be used actively by teachers and teacher educators to more carefully orchestrate demands that various sponsors of literacy have toward their own ends.
Keywords: Literacy; sponsors; sponsors of literacy; high school English; classroom research